A Ni(OH)2 nanopetals network for high-performance supercapacitors synthesized by immersing Ni nanofoam in water - Zheng, Donghui; Li, Man; Li, Yongyan; Qin, Chunling; Wang, Yichao; Wang, Zhifeng (Beilstein Journal of Nanotechnology, 2019)
Developing a facile and environmentally friendly approach to the synthesis of nanostructured Ni(OH)2 electrodes for high-performance supercapacitor applications is a great challenge. In this work, we report an extremely simple route to prepare a Ni(OH)2 nanopetals network by immersing Ni nanofoam in water. A binder-free composite electrode, consisting of Ni(OH)2 nanopetals network, Ni nanofoam interlayer and Ni-based metallic glass matrix (Ni(OH)2/Ni-NF/MG) with sandwich structure and good flexibility, was designed and finally achieved. Microstructure and morphology of the Ni(OH)2 nanopetals were characterized. It is found that the Ni(OH)2 nanopetals interweave with each other and grow vertically on the surface of Ni nanofoam to form an “ion reservoir”, which facilitates the ion diffusion in the electrode reaction. Electrochemical measurements show that the Ni(OH)2/Ni-NF/MG electrode, after immersion in water for seven days, reveals a high volumetric capacitance of 966.4 F/cm3 at a current density of 0.5 A/cm3. The electrode immersed for five days exhibits an excellent cycling stability (83.7% of the initial capacity after 3000 cycles at a current density of 1 A/cm3). Furthermore, symmetric supercapacitor (SC) devices were assembled using ribbons immersed for seven days and showed a maximum volumetric energy density of ca. 32.7 mWh/cm3 at a power density of 0.8 W/cm3, and of 13.7 mWh/cm3 when the power density was increased to 2 W/cm3. The fully charged SC devices could light up a red LED. The work provides a new idea for the synthesis of nanostructured Ni(OH)2 by a simple approach and ultra-low cost, which largely extends the prospect of commercial application in flexible or wearable devices.
Keywords: dealloying; Ni nanofoam; Ni(OH)2 nanopetals; metallic glass; supercapacitor